Uterine scoring system for reproduction scoring correlation with pregnancy rate in infertility patients undergoing intracytoplasmic sperm injection and embryo transfer - Shivtare, Mamta Vijay; Lad, Nikita; Vishwekar, Pallavi; Shetty, Pradnya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Infertility is defined as failure to conceive a clinical pregnancy after 12 months or more of regular unprotected intercourse. The birth of Louis Brown opened door to whole new world. Science of reproduction unfolded with better understanding of physiology and pharmacology of gonadotropins. Improved stimulation protocol, and lab facilities are available for IVF and intracytoplasmic sperm injection (ICSI). The objective of this study was to study relation between uterine scoring system for reproduction (USSR) scoring and pregnancy rate in patients undergoing ICSI and embryo transferred. Methods: A prospective observational study was conducted. Study comprised 48 women visiting with infertility for ICSI and embryo transfer. Baseline scan done on day2 of menses. Patients started on estradiol valerate for endometrial preparation. Transvaginal sonography done on 10th day of menstrual cycle for USSR scoring. USSR scoring includes parameters such as endometrial thickness, endometrial layering, myometrial contractions, myometrialechogenecity, uterine artery Doppler flow, endometrial blood flow, myometrial blood flow. Results: Out of total 48 infertility patients for embryo transfer 22 conceived, which gives 45.83% pregnancy rate. No patients had a perfect score of 20. Patients with score of 17-19 had pregnancy rate of 66%. Endometrial thickness of 10-14mm gave optimum result of 52%. Pulsatality index <2.19 was associated with pregnancy rate of 66%. Conclusions: USSR scoring is highly indicative of good pregnancy outcome in patients undergoing ICSI and embryo transfer. Endometrial morphology and thickness was strongly correlated with successful pregnancy outcome.